IPad the missing manual - Pogue, David (O'Reilly Media, 2014)
OS 8 for the iPad is the biggest iOS release ever, and this all-new Missing Manual includes everything you need to know about iPadu2019s exciting features and new user interface. Missing Manual series creator David Pogue takes you on a guided iPad tour, complete with step-by-step instructions, crystal-clear explanations, and lots of tips, tricks, and surprises along the way.